Comparative evaluation of apical sealing ability of different root canal sealers - Halenur Altan; Zeynep Göztaş; Gülsüm İnci; Gül Tosun (Istanbul University, 2018)
Purpose The aim of this study was to compare the short and long term apical sealing ability of different root canal sealers. Materials and methods Fifty-five extracted human anterior single-root teeth were used. The coronal part of each tooth was removed and the root canals were prepared with NiTi rotary instruments. Teeth were divided into 5 study groups; Group I: MTA Fillapex (Angelus, Brazil); Group II: Sealapex (Sybron-Kerr, Romulus, MI, USA) and Group III: AH Plus (Dentsply, Konstanz, Germany) (n=15) and negative and positive control groups (n=5). The quality of root canal sealing was assessed by a fluid filtration method performed at 24 h and 180-day time intervals. Kruskal Wallis and Mann Whitney U tests were used to compare the groups. Results At 24 h evaluation, MTA Fillapex presented significantly less microleakage than the Sealapex and AH Plus (p<0.05). At long term interval (180-day), Sealapex and AH Plus presented significantly less microleakage than the MTA Fillapex (p<0.05). Conclusion Sealapex and AH Plus showed significantly better sealing abilities than MTA Fillapex in the long term.